Ethnic diversity and mortality in northwestern Burkina Faso: a cohort analysis from 2000 to 2012. (20th October 2021) - Wasko, Z; Dambach, P; Kynsat-Wolf, G; Steiglbauer, G; Zabré, P; Bagagnan, C H; Schoeps, A; Souares, A; Winkler, V
Abstract: Background: Ethnic diversity has been a topic of contention across the globe, contrasted with economic development, social security, and political stability. The link between health and ethnic diversity is not yet well established. This study aims to explore the association between ethnic diversity and all-cause mortality. Methods: We used data from the Nouna Health & Demographic Surveillance System (HDSS) collected between 2000 and 2012. To derive Standardized Mortality Ratios (SMR), the observed number of deaths for each village was compared to the expected deaths based on the whole HDSS accounting for sex, age, rainy season, calendar year, and village. SMR were calculated on a village level for ethnic diversity (using the Simpson Index), geographical region, wealth, distance to Healthcare Facility (HCF), and religious diversity (Simpson Index). Also, we modeled SMR with a multilevel random intercept Poisson model considering individual ethnic and religious groups in addition to the above-mentioned village-level information. Results: Village wealth (poorest quintile: SMR 1.07; 95% CI: 1.02-1.13, richest quintile: SMR 0.85; 95% CI: 0.82-0.88), distance to HCF (within the village: SMR 0.88; 95% CI: 0.85-0.91, further than 5km: SMR 1.13; 95% CI: 1.10-1.16), and village geographical region showed significant associations with overall mortality. Villages in the high ethnic diversity tertile had a lowered SMR (0.86; 95% CI: 0.84-0.89) compared to the overall HDSS, while those with low diversity yielded an elevated SMR (1.13; 95% CI: 1.09-1.17). The multivariable model including all co-variables confirmed the association. Conclusions: This study shows a link between ethnic diversity and health. Historically established ethnic diversity in rural areas of Burkina Faso is associated with lower all-cause mortality. A lack of standardization exists in defining and measuring ethnic diversity. More research is needed to understand this relation and to establish it in different settings. Key messages: Ethnic diversity is potentially linked to health. Further studies in different settings are needed to fully understand the relation between ethnic diversity and health.